Capital Mobility in ASEAN Country - Singh, Sanjay Kumar (2016)
ASEAN Countries as emerging market are a hot destination for investment other than US, Europe, China, Japan and many other markets. Majority of investment after 1985 shifted towards Asian market (Beams, 2002), “EAT” as new destination. Thereafter ASEAN countries offer challenges to US, European Union and Japanese market in terms of investment. Investment also carry financial crisis, thereby ASEAN countries are not behind getting impacted due to financial crisis. Sudden change in capital flow direction bring financial instability, which result into financial crisis. In last two decade ASEAN countries has seen two major financial crisis due to huge capital inflow and outflow from one countries to others. Therefore this paper have been design to review the role of capital mobility in ASEAN Countries by applying different econometric tools to measure their impact on key financial drivers. Financial impact measurement had been carried out using Peter Montiel and Feldstein Horioka (FH) methodology and theory. Here capital mobility have been split to measure trade and capital at separate level. Trade are being measured using trade ratio and capital flow using capital flow ratio against percentage of GDP growth. Measurement of “Saving and Investment” over capital flow using FH theory. Analysis had been carried out to evaluate the role of exchange rate, interest rate and their response. Analysis has been conducted after splitting 16 countries into 3 major groups and analysed them over pre and post financial crisis (2007-08) period. Research cover what impact does EXC, INT, CAB, FDI, GDP, MS2 and TRG will bring over TR and CFR. Analysis result suggest that CAB, EXC, FDI and MS2 play pivot role in initiating capital mobility within group. Small change in EXC result in capital flow, which can be treated as crisis alarm. Twin financial crisis in last two decade had impacted ASEAN countries the most. One group of ASEAN (Minor) countries heavily impacted without being fully integrated. ASEAN Economic Community already working towards ASEAN regional integration followed by global integration for free trade and services. Research paper advocate for strong and controlled policy prior to opening of ASEAN economic to global market. Control policy vision and implementation should reduce capital inflow and outflow from local market. Policy should have check on Private Bankers and Investors to have regulated capital flow, which will provide confidence to investors in future run. Control capital will boost investor confidence in country economy and will avert future financial crisis.